Fifteen-level multilevel inverter with reduced active power semiconductor switches and real-time switching-angle calculation technique - Soo, Jian Aun (School of Electrical System Engineering, 2018)
To address the problem stated in previous section, this work aims to develop a 15-level CHBMI with reduced active power semiconductor switches and real-time switching-angle calculation technique for wide modulation index operation. A simulation model and a prototype have been developed to evaluate the performance of the proposed CHBMI such as the THD over wide modulation index, power losses and real-time response of the proposed switching-angle calculation technique.